2016
DOI: 10.1108/bfj-03-2015-0101
|View full text |Cite
|
Sign up to set email alerts
|

Price-quality heuristic correlation with rates of product consumption

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…More recent studies have found evidence of the manifestation of price affect. Priilaid and Hall (2016) found that price affect strengthens across increasing rates of product consumption, whereas others have observed that this increases with levels of consumer expertise and experience (Priilaid, Sevenoaks, Aitken, & Chisholm, 2013;Priilaid & van Rensburg, 2016). Both studies suggest that the way in which individuals respond to a product when consumed in sighted tasting experiments will depend on the price of the product.…”
Section: What Is the Price-quality Framing Effect?mentioning
confidence: 92%
“…More recent studies have found evidence of the manifestation of price affect. Priilaid and Hall (2016) found that price affect strengthens across increasing rates of product consumption, whereas others have observed that this increases with levels of consumer expertise and experience (Priilaid, Sevenoaks, Aitken, & Chisholm, 2013;Priilaid & van Rensburg, 2016). Both studies suggest that the way in which individuals respond to a product when consumed in sighted tasting experiments will depend on the price of the product.…”
Section: What Is the Price-quality Framing Effect?mentioning
confidence: 92%
“…Therefore, a dynamic analysis of prices as consumer ratings change is not possible. Moreover, wine prices and quality perception are closely connected (Priilaid and Hall, 2016), and Vivino users usually know the price when rating a wine. Figure 3 supports this relationship, showing how the average consumer rating increases as more expensive wines are considered.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the generally perceived meaning, that products labelled by quality marks are generally accepted to be of higher quality, the findings of disorientation among all the labels and distrust of brands has been recognised among generation Y customers. Together with massive brands expansion comes also the ignorance of labels (Heerwagen, et al 2015, Altintzoglou, Heide, 2016, Priilaid, Hall, 2016, Grunert, Aachmann, 2016, Velčovská, Hadro, 2018. The data of organic food consumption conducted on previous different generations might not be generalized also to generation Y due to their unique consumption behavior and preferences (Khan, Mohsin, 2017, Macready, at al.…”
Section: Literature Reviewmentioning
confidence: 99%